2018
DOI: 10.3390/molecules23092163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Dalbergia Species Based on Differences in Extractive Components

Abstract: Dalbergia cultrate, Dalbergia latifolia, and Dalbergia melanoxylon are precious and valuable traded timber species of the genus Dalbergia. For chemotaxonomical discrimination between these easily confused species, the total extractive content of the three wood species was determined using four different organic solvents. Fourier transform infrared (FTIR) spectroscopy was used to analyze functional group differences in the extractive components, inferring the types of principal chemical components according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
(37 reference statements)
1
31
0
Order By: Relevance
“…These values were in the range of extraction efficiency of various wood materials. Generally, wood extractives account for 2% to 5% of wood content, even though higher yields could be reached in certain types of wood or by different extractants . For example, Malik and Santoso reported extraction efficiencies in the range of 0.7% to 6.7% for oily keruing wood samples using solutions of water and ethanol in various proportions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were in the range of extraction efficiency of various wood materials. Generally, wood extractives account for 2% to 5% of wood content, even though higher yields could be reached in certain types of wood or by different extractants . For example, Malik and Santoso reported extraction efficiencies in the range of 0.7% to 6.7% for oily keruing wood samples using solutions of water and ethanol in various proportions.…”
Section: Resultsmentioning
confidence: 99%
“…This was because the higher extractive contents associated with lower crystallinity and lower cellulose crystallite size could accelerate the degradation process . While wood extractives may include an array of compounds (eg, aliphatic, terpenoid, and phenolic) in nature, the detailed characterization of their molecular compositions by advanced instrumental techniques is very limited …”
Section: Introductionmentioning
confidence: 99%
“…In this study, EB showed a significantly higher extraction rate than WT: 16.12% (EB) and 1.89% (WT) on average ( Table 1). The ethanol/benzene-soluble extractives comprising over 16 wt% of ABW heartwood (Table 1) [22], apparently have a large impact on ABW deformation characteristics.…”
Section: Deformation Characteristicsmentioning
confidence: 99%
“…The quantity of extractives in ABW heartwood has been estimated to be over 15 wt% in ethanol/benzene (1:2 v/v) solvent extraction, which is much higher than in other Dalbergia species, such as Dalbergia cultrate and Dalbergia latifolia [22]. The high concentrated extractives potentially work to promote flow deformation by heating beyond the thermal softening point of them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation